Approaches to the Lithuanian Folk Ballad in the Second Half of the 20th Century - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2023)
This historiographic survey strives to demonstrate the considerable attention that the Lithuanian folk-ballads received in the second half of the 20th century. The historiographic material is presented systematically, while employing contextual data as well. Thus, Jonas Balys continued in emigration his interwar research of the ballads; in 1954 he published the catalogue of the “Lithuanian Narrative Folksongs”, and continued to keenly follow latest developments in Lithuania and review folklore studies. In Germany, Erich Seemann published in 1951 his research on the connections between the German and the Lithuanian folksongs, where he also discussed migration of ballads. On this side of the Iron Curtain, Pranė Jokimaitienė reflected on the works by Balys and other colleagues. In the monographs published during the Soviet-period, ballads were to some extent touched upon by Danutė Krištopaitė (1965), Jadvyga Čiurlionytė (1966), and Donatas Sauka (1970). In 1966, Vladimir Toporov published an article on the structure of the Lithuanian ballads. In 1968, a comprehensive study by Jokimaitienė was published, establishing in our folkloristics the canonic paradigm of ballad research, which has remained valid till the present day. The author of this article seeks to reveal the various ways of the paradigm of ballad research becoming entrenched in Lithuanian folkloristics during that time. The mosaic of approaches to Lithuanian ballads shows the prevalence of the above-mentioned paradigm as a process which several folklore researchers were engaged with. Insights and studies from that period have remained relevant to the contemporary ballad researchers.
Keywords: ballads; Jonas Balys; Pranė Jokimaitienė; folkloristics; second half of the 20th century